Research methodology of personal and professional qualities of the teacher’s value-motivational conflict - Voloshchuk, Serhiy; Rati, Oksana; Odarchenko , Veronika; Astremska, Iryna; Tyvodar , Andrii (My University, 2024)
Objective: This study explores the value-motivational conflicts among higher education teachers, focusing on the personal and professional determinants that influence these conflicts. Methods: Utilizing a comprehensive review of psychological and pedagogical literature, this research delineates the concept of value-motivational conflict, its definition, and essential features. The study identifies stable relationships between values and motives within the value-motivational sphere of higher education teachers, categorizes the types and levels of conflicts, and investigates the determinants influencing these conflicts. Results: The findings highlight the significant role of both personal and professional factors in shaping the value-motivational conflicts experienced by teachers. It emphasizes the need for a deeper understanding of these conflicts to enhance the effectiveness of educational processes. Conclusion: The research contributes to the theoretical framework of pedagogical psychology by deepening the understanding of intrapersonal conflicts' structure and types within the teaching profession. It underscores the necessity of addressing these conflicts to improve teachers' professional functioning and well-being.
Keywords: ціннісно-мотиваційний конфлікт; викладачі закладів вищої освіти; педагогічна психологія; внутрішньо особистісний конфлікт; ефективність навчання; value-motivational conflict; higher education teachers; pedagogical psychology; intrapersonal conflict; educational effectiveness